Is there room for interculturality? Indigenous youth in Peruvian private universities and the scholarship programme Beca 18 - (:unkn) unknown (Informa UK Limited (Taylor & Francis), 2024)
Applying an ethnographic approach, this study examines recently implemented scholarship programmes for Indigenous people in private higher education (HE) institutions in Peru. Interviews with students and staff, participant observations, and participator...
Keywords: Interculturalidad; Educación superior